Hak-Hak Dan Konsekuensi Hukum Bagi Seorang Yang Telah Diputus Lepas dari Segala Tuntutan dan Rehabilitasinya Dalam Proses Hukum (Studi Di Pengadilan Negeri Kelas IA Khusus Surakarta) - Utomo, Danang Yogo; , Hartanto, S.H, M.Hum (2017)
The main objective of this study was to research the right`s and legal consequences for a person who has been in breaking free from all claims and rehabilitation in the proceedings, namely the certainty of law for a person who is being or has been doing legal proceedings. To determine the implementation of the right`s to a free from all claims that have been cut off and given rehabilitation, as well as barriers or obstacles that occur in the process of implementation of the provision of rehabilitation. This research method using descriptive empirical approach. Using this type of primary data and secondary data. Using literature data collection techniques, interviews. By using qualitative data analysis. Results obtained from this research is to know the implementation of rehabilitation and obstacles that arise in the legal process, understand and develop a theory that was obtained.